EFEKTIVITAS PERATURAN PEMERINTAH NOMOR 54 TAHUN 2007 TENTANG PELAKSANAAN PENGANGKATAN ANAK (Studi di Kecamatan Narmada, Kabupaten Lombok Barat) - Ni Nyoman Sri Sukma Mega Viedny; Lalu Hadi Adha (Private Law, 2021)
This research aims to find out the effectivity of the Government regulation number 54 of 2007 concerning the practice of children adoption at sub-district Narmada, Lombok Barat regency as well as to find out causing factors that prevent people to adopt children based on the regulation. Applied research type is normative-empirical. Research result indicates that all adoption practice by the people of Narmada are conducted under written or oral agreement, which only 20 % or 3 families conducted the adoption in accordance with the regulation. Meanwhile, causing factors that prevent Narmada people from adopting children based on the regulation are including the lack legal socialization of the regulation leads to the lack understanding on it. From the citizens side, there is a stigma or perception that legal children adoption through court and adat institution decision is complicated and expensive.